Taxonomy of the freshwater crab Coccusa cristicervix Ng & Grinang, 2004 (Decapoda: Brachyura: Gecarcinucidae), with description of a new species of Thelphusula from Sarawak, Malaysia, Borneo - Grinang, J.; Ng, P.K.L (Raffles Bulletin of Zoology, 2014)
The taxonomy of the Sarawakian gecarcinucid freshwater crab Coccusa cristicervix Ng & Grinang, 2004, is revised with the recent discovery of males, and the species is transferred to Thelphusula Bott, 1969. The male abdomen, fi rst and second gonopods are described and fi gured for the fi rst time. A new species, Thelphusula pueh, is also described from swampy habitats in Kampung Sebako in Pueh, Lundu District, Sarawak.